A Combined Transition‐Metal‐Catalyzed and Photopromoted Process: Synthesis of 2, 3‐Fused 4‐Phenylnaphthalen‐1‐yl Carboxylates from 1, 7‐Diaryl‐1, 6‐diynes. Issue 25 (15th May 2015) - Yamamoto, Yoshihiko; Mori, Shota; Shibuya, Masatoshi
Abstract 2, 3‐Fused 4‐phenylnaphthalen‐1‐yl carboxylates were synthesized in a step‐ and atom‐economical manner using a ruthenium‐catalyzed hydrocarboxylative cyclization of 1, 7‐diaryl‐1, 6‐diynes and subsequent oxidative photocyclization. The scope of this novel two‐step process was demonstrated by the construction of diverse structures from substrates with various tethers and terminal aryl groups. Late‐stage CH functionalizations of the arylnaphthalene product further enhance the synthetic potential of the developed process.